2017
DOI: 10.1371/journal.pone.0173068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cash transfers and vouchers on the use and quality of maternity care services: A systematic review

Abstract: BackgroundCash transfers and vouchers are forms of ‘demand-side financing’ that have been widely used to promote maternal and newborn health in low- and middle-income countries during the last 15 years.MethodsThis systematic review consolidates evidence from seven published systematic reviews on the effects of different types of cash transfers and vouchers on the use and quality of maternity care services, and updates the systematic searches to June 2015 using the Joanna Briggs Institute approach for systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 63 publications
(154 reference statements)
6
88
2
Order By: Relevance
“…12 A systematic review done by Hunter BM shows cashless transfer helps the mother utilize maternity services and increase institutional deliveries. 16 A higher percentage of respondents used JSY in our study compared to NFHS 4 and the Rajasthan study. As this was a more recent study, implementation of JSY may have improved.…”
Section: Antenatal Care Utilizationcontrasting
confidence: 52%
“…12 A systematic review done by Hunter BM shows cashless transfer helps the mother utilize maternity services and increase institutional deliveries. 16 A higher percentage of respondents used JSY in our study compared to NFHS 4 and the Rajasthan study. As this was a more recent study, implementation of JSY may have improved.…”
Section: Antenatal Care Utilizationcontrasting
confidence: 52%
“…Numerous cash transfer schemes in SEAR countries facilitate the maternal and childcare including institutional deliveries as detected in our review. It is tally with Hunter et al in their consolidated systematic review 74 . Contracting nongovernment health providers is an important step in reducing maternal mortality in India.…”
Section: Discussionmentioning
confidence: 64%
“…Ours is one of the few studies to examine the effect of demand side financing on quality of care (Hunter, Harrison, Portela, & Bick, 2017) with only one quasi-experimental study identified reporting improvements on postnatal quality in Kenya (Watt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%